Milly, Molly AND BEEFY - Pittar, Gill (Scholastic Sydney, 2001)
"The Milly, Molly series of books are stories about values, and have been written to promote the acceptance of diversity and sound values for character education"--Page iv, Teacher's resource books 3 and 4